1973
DOI: 10.1073/pnas.70.8.2291
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence for a Microsomal Precursor to Human Parathyroid Hormone

Abstract: Human parathyroid glands from a patient with chronic renal failure were used to study in vitro biosynthesis of immunoreactive parathyroid hormone. Parathyroid glands were incubated in the presence of [3Hlleu-cine, and classical subcellular fractions were prepared. Peptides from acetic acid extractions of the fractions were separated on Sephadex G-75 Superfine. Eluates were assayed for immunoreactive parathyroid hormone by a double-antibody technique. Leucine was incorporated into several large immunoreactive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1974
1974
1980
1980

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Wong and Lindall (29) and Benson et al (30) recently reported findings that are consistent with the production and secretion of immunoreactive molecular forms larger than PTH.…”
Section: Introductionsupporting
confidence: 63%
“…Wong and Lindall (29) and Benson et al (30) recently reported findings that are consistent with the production and secretion of immunoreactive molecular forms larger than PTH.…”
Section: Introductionsupporting
confidence: 63%
“…The absence of a methionine residue (the initial residue believed to be involved in translation in eukaryotic systems (see Kemper et al, 1976)) preceding the amino terminus of ProPTH makes it extremely unlikely that initiation of polypeptide chain growth occurs with the synthesis of a molecule as small as ProPTH. On the other hand, it also is possible that precursors of PTH larger than Pre-ProPTH exist that are synthesized and secreted into the circulation under abnormal conditions (Wong and Lindall, 1973;Benson et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…It seems possible that under unusual circumstances pre-ProPTH may not be cleaved and may accumulate in the cell or even be secreted. Several large proteins, immunoreactive to PTH antisera, have been found in hyperplastic parathyroid tissue (23) and in blood of patients with ectopic hyperparathyroidism (24). Pre-ProPTH may correspond to one of the immunoreactive species noted in these studies.…”
Section: Methodsmentioning
confidence: 99%